Shoulder biomechanics of para-table tennis: a case study of a standing class para-athlete with severe leg impairment - Pui Wah Kong; Jia Wen Yam (BMC, 2022)
Abstract Background Both able-bodied and Class 7 para-table tennis players compete while standing, but do they use the same techniques to hit the ball? This case study examined the shoulder joint kinematics of a highly skilled para-table tennis player with severe leg impairment. Methods One international level Class 7 male para-table tennis player was compared with a control group of 9 male, competitive university team players. Participants performed 15 trials of forehand and 15 trials of backhand topspin drives. Shoulder abduction/adduction angles and joint range of motion (ROM) were measured using an inertial measurement system. Results The joint ROM of the para-player was comparable to the control group in the forehand [para-player 38°, controls 32 (15)°] and slightly larger in backhand [para-player 35°, controls 24 (16)°]. Waveform analysis revealed significant differences in the entire forehand drives (p < .001) and the preparation (p < .001) and follow-through phases (p = .014) of the backhand drives. Conclusions Coaches should not simply instruct para-table tennis players to replicate the characteristics of able-bodied players. Depending on the nature of the physical impairment, para-players should optimise their movement strategies for successful performance.